Synthesis and UCST-type thermoresponsive properties of polypeptide based single-chain nanoparticles. Issue 38 (13th September 2019) - Zhao, Liang; Wang, Xiaodan; Sun, Liwei; Zhou, Rongtao; Zhang, Xu; Zhang, Lin; Zheng, Zelai; Ling, Ying; Luan, Shifang; Tang, Haoyu
Abstract : We present the synthesis and UCST-type thermoresponsive properties of helical polypeptide based single-chain nanoparticles which displayed increased solution phase transition temperature and improved biocompatibility. Abstract : Polypeptide based single-chain nanoparticles (SCNPs) were synthesized via intramolecular crosslinking between ABA-type triblock copolymers and 1, 4-diiodobutane in dilute solution (0.25 mg·mL −1 ). Alkylation of the thioether containing SCNPs in the presence of propargyl bromide yielded sulfonium containing SCNPs with "clickable" alkyne pendants, which can be readily modified by azido compounds. Copper-mediated 1, 3-dipolar cycloaddition between the alkyne containing SCNPs and (3-azidopropyl)triphenylphosphonium bromide (TPP-N3 ) afforded SCNPs bearing TPP pendants. An ion-exchange reaction endowed the TPP containing SCNPs with tunable hydrophilicity/hydrophobicity by adjusting the types of counteranions. All the resulting polypeptide based SCNPs adopt α-helical conformation in both the solid-state and solutions. SCNPs bearing triphenylphosphonium iodide formed self-assembled structures in aqueous solutions and showed upper critical solution temperature (UCST)-type thermoresponsive properties. The UCST SCNPs showed increased UCST-type phase transition temperature ( T pt ) and improved biocompatibility compared to their linear polymer counterparts. The T pt increased by intrachain crosslinking, increasing the crosslinking density or concentration. Our work provides a new and facile route to prepare side-chain "clickable" and α-helical SCNPs.